2012
DOI: 10.1523/jneurosci.0251-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5 Regulates the Polarized Trafficking of Neuropeptide-Containing Dense-Core Vesicles in Caenorhabditis elegans Motor Neurons

Abstract: The polarized trafficking of axonal and dendritic proteins is essential for the structure and function of neurons. Cyclin-dependent kinase-5 (CDK-5) and its activator CDKA-1/p35 regulate diverse aspects of nervous system development and function. Here, we show that CDK-5 and CDKA-1/p35 are required for the polarized distribution of neuropeptide-containing dense-core vesicles (DCVs) in C. elegans cholinergic motor neurons. In cdk-5 or cdka-1/p35 mutants, the predominantly axonal localization of DCVs containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
103
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 74 publications
18
103
1
Order By: Relevance
“…In C. elegans DA and DB motor neurons, the commissures extend from the cell somas on the ventral side of the animal across the body to the synaptic region of the axon in the dorsal nerve cord ( Figure 6A). The concentration of DCVs in a wild-type commissure is much lower than in the synaptic region, and time-lapse imaging studies suggest that many fluorescently tagged neuropeptide puncta within commissures represent individual vesicles or packets of cotransported vesicles (Goodwin et al 2012; also supported by Figure 10 in this study).…”
Section: Dcvs Largely Fail To Enter Axons In Unc-43 Lf Mutantssupporting
confidence: 76%
See 3 more Smart Citations
“…In C. elegans DA and DB motor neurons, the commissures extend from the cell somas on the ventral side of the animal across the body to the synaptic region of the axon in the dorsal nerve cord ( Figure 6A). The concentration of DCVs in a wild-type commissure is much lower than in the synaptic region, and time-lapse imaging studies suggest that many fluorescently tagged neuropeptide puncta within commissures represent individual vesicles or packets of cotransported vesicles (Goodwin et al 2012; also supported by Figure 10 in this study).…”
Section: Dcvs Largely Fail To Enter Axons In Unc-43 Lf Mutantssupporting
confidence: 76%
“…In C. elegans DA and DB motor neurons, the commissures extend from the cell somas on the ventral side of the animal across the body to the synaptic region of the axon in the dorsal nerve cord ( Figure 6A). The concentration of DCVs in a wild-type commissure is much lower than in the synaptic region, and time-lapse imaging studies suggest that many fluorescently tagged neuropeptide puncta within commissures represent individual vesicles or packets of cotransported vesicles (Goodwin et al 2012; also supported by Figure 10 in this study).We compared the number of detectable fluorescent puncta containing soluble and aggregated neuropeptide cargos in wild-type and unc-43 lf mutant commissures. In the ventral commissure region, which is the closest region to the cell soma, the number of detectable puncta containing soluble cargo and aggregated neuropeptide cargo in an unc-43 lf mutant was reduced by 63 and 82%, respectively (Figure 6B).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Toll-like receptor 4 induces remodeling via phosphorylation of the myosin light chain for the release of microparticles, thus regulating tumor inflammatory microenvironment (17). Goodwin et al (18) reported that, in motor neuron cells, CDK-5 regulates microtubule orientation and in cancer, Strock et al (8) reported that inhibiting the activity of CDK5 resulted in changes in the microtubule cytoskeleton, loss of cellular polarity and loss of motility in prostate cancer. In the present study, inhibition of CDK5 resulted in failed microtubule assembly, thus leading to impaired mobility of the A549 lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%